2015
DOI: 10.36876/smjo.1012
|View full text |Cite
|
Sign up to set email alerts
|

Subtalar Dislocation Associated with a Ruptured Tibialis Posterior Tendon: A Rare Case Report

Abstract: We report a case on a rare ankle injury which occurred after an opened trauma of the left ankle, associating a lateral subtalar dislocation with a ruptured tibialis posterior tendon. We treated him surgically with a good evolution clinic and radiological. Figure 1 a: Clinical aspect of a subtalar dislocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(9 reference statements)
0
0
0
Order By: Relevance
“…To the best of our knowledge, this is the first case reporting such a complication resulting from a closed medial subtalar dislocation. A previous report by Boussakri et al reported a rupture of this tendon following an open lateral subtalar dislocation [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first case reporting such a complication resulting from a closed medial subtalar dislocation. A previous report by Boussakri et al reported a rupture of this tendon following an open lateral subtalar dislocation [ 10 ].…”
Section: Discussionmentioning
confidence: 99%